(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The term intentionality has remained obscure since the ninth century AH, when Al-Sharif Al-Jurjani (740-816 AH, 1339-1413 AD) mentioned it in his encyclopedia (The Book of Definitions), until it was brought back to mind by the philosopher (Francis Brentano (1917-1838), and then its scope was narrowed by the late linguist Sibit Al-Nili. In the language, intentionality means that single words are given their single meanings in an intentional and inevitable manner, and one word cannot cover another word, except in a specific context, such as the Almighty’s saying: “You are the best nation” and “and remembered after a time” and that Abraham was a nation. “We notice that the word (nation) has limited meaning to a group that meets in a fateful unity, but the linguistic and functional clues have suggested a new meaning, According to most commentators, the first means (the group), the second takes on the meaning of (duration), and the third stops at the meaning of (the role model and the imam); The context in the noble verses clothed the word with new analysis and connotations, thus inspiring the functional relationships in the phrase. When words are used singularly, they are intended for themselves, as if they were independent, non-colonized countries that possessed their own components, without relying on others. Therefore, when interpreting a word with another word, this is a kind of distortion or approximation, or what is termed as (interpretation), and the closest interpretation of a word is with a set of words and not with another word. Intentionality is essentially a mental property that expresses an orientation or attachment. Its task is mental representation, that is, the mind’s ability to represent things. The intention in the noble verse or any literary text becomes clear through the linguistic structure, in addition to its great impact in the study of emotion, as it is a special state of the mind (desire, belief, hope, and judgments about things). We will examine its patterns and uses in the Glorious Qur’an. The Qur’anic text is a religious text whose source is Allah - Glory be to Him - and its goal is to elevate man and bring him to the highest levels of perfection. Therefore, the Qur’anic text is considered a text of guidance, Alla Almighty said: “This is the Book about which there is no doubt, a guidance for those conscious of Allah.” Al-Baqarah 2,In addition, the Qur’anic text has unleashed the energies of the language and mobilized its rules and arts in getting closer to it and realizing its textual goals. Ali bin Abi Talib - may Allah honor his face - said: “The surface of the Qur’an is elegant and its interior is deep. Its wonders do not fade away, its strange things do not disappear, and darknesses are not revealed except through it.” His words were interpreted by some theological groups as saying that the Noble Qur’an has an outer and a inner part. This is what he does not aim for and does not concern him - may the best prayers and peace be upon him -. Rather, he wanted to describe the Qur’an in the language of his time, pointing to the apparent significance and the deep significance in seeking meanings and the human, scientific and jurisprudential dimensions that the text suggests.